FAKTOR-FAKTOR YANG DIPERTIMBANGKAN OLEH NASABAH DALAM MENGADOPSI SISTEM LAYANAN ONLINE BANKING (Fokus Ekonomi, 2010)
This paper report factors that influence banking customer for adopting online banking. Attitude and acceptance of a new system will impact to the successful for the adoption of that system. Technology acceptance model (TAM) has been a popular model for adoption of information system because of its parsimony. Using regression analysis, the result shows that only perceived usefullness and perceived credibility that influence the customer for using online banking.